Carbon‐Assisted Stable Silver Nanostructures. Issue 23 (21st October 2020) - Abdollahi, S. Narjes; Ochoa Martínez, Efraín; Kilchoer, Cédric; Kremer, Geoffroy; Jaouen, Thomas; Aebi, Philipp; Hellmann, Tim; Mayer, Thomas; Gu, Yibei; Wiesner, Ulrich B.; Steiner, Ullrich; Wilts, Bodo D.; et al.
Abstract: Nanostructured silver stands out among other plasmonic materials because its optical losses are the lowest of all metals. However, nanostructured silver rapidly degrades under ambient conditions, preventing its direct use in most plasmonic applications. Here, a facile and robust method for the preparation of highly stable nanostructured silver morphologies is introduced. 3D nanostructured gyroid networks are fabricated through electrodeposition into voided, self‐assembled triblock terpolymer scaffolds. Exposure to an argon plasma degraded the polymer and stabilized the silver nanostructure for many weeks, even in high humidity and under high‐dose UV irradiation. This stabilization protocol enables the robust manufacture of low‐loss silver nanostructures for a wide range of plasmonic applications. Abstract : Nanostructured silver has the lowest optical losses of all noble metals, but rapidly degrades under ambient conditions, limiting its utility. Graphitic layers can stabilize silver, and such protecting layers form upon argon plasma etching silver embedded in nanostructured polymer templates. This facile process stabilizes nanostructured silver for weeks even in harsh environments, enabling a wide range of plasmonic applications.